UPAYA PENINGKATAN PRODUKTIVITAS TENAGA KERJA KONTRAKTOR DI WILAYAH KABUPATEN PASER, KALIMANTAN TIMUR - Vera Victya (Jurnal Teknologi Berkelanjutan, 2018)
Productivity is very important for every worker in completing a job. High work productivity must be possessed by every worker in all construction sectors. High labor productivity is needed for the success of construction projects. High and low work productivity of the labor force greatly affects the time of the construction project implementation. The level of labor productivity is influenced by many factors including age, work experience / years of work, labor expertise, education level, wage suitability, worker health, field / weather conditions, work group composition and relationships between workers. All of these variables have a large influence on labor productivity on brickwork. From the results of this study found the level of productivity of the brickwork at a height of 0 floors to 50 cm at 1.42 m2 / hour, at a height of 50 cm to 2 meters at 2.20 m2 / hour, at a height of 2 meters to 3.5 meters at 1.95 m2 / hour, and at an altitude of 3.5 meters to 6 meters at 1.70 m2 / hour. Efforts that must be made in increasing labor productivity are to tighten supervision of the worker so that they can work optimally and the need for worker training to obtain a certificate of expertise so that the contractor have workers with good skill.